Aplikasi Edible Film dari Rumput Laut Eucheumma cottoni dan Pati Sorgum dengan Plasticizer Gliserol dan Filler CacO3 sebagai Bahan Pembuat Cangkang Kapsul - Yuli Darni; Fakih Aulia Rakhman (Balitbangda Provinsi Lampung, 2017)
Edible film was a thin layer used to coat a food that serves as a barrier of mass transfer such as moisture, oxygen, fat, and lightandalso servedas a food additive carrier. Edible films wereused in various fields, such as pharmaceutical which used edible film as a coating of drug (capsule shells). The study was conducted on the production of edible film as capsule shell from seaweed Eucheumma cottoni and sorghum starch with the addition of CaCO3 as filler and glycerol as plasticizer with gelatinization temperature at t = 95 ° C. The total weight of starch:seaweed (9:1, 8:2, 7:3,and6:4, respectively) was 10 g with 10 % (g/g) glycerol as plasticizer and CaCO3 as filler which varied as 0, 0.2 , 0.4, and 0.6 % (g/g), respectively. The mixture was stirred for 35 minutes with stirring speed of 380 rpm. The result indicated that the best composition of starch:seaweed was 60:40 with 0,4 % CaCO3 resulted in the edible film having tensile strength 11,12 Mpa, extension 3.14 %, and modulus Young 353.11 Mpa and water content of 11.39 % and ash content 5.66%.